EFFECT OF LAUGHTER THERAPY ON BLOOD PRESSURE PATIENTS WITH ESSENTIAL HYPERTENSION - SF Jalali (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: Using humor to decrease stress, diminish pain and improve quality of life has recently become a popular topic. Job and life stress were effective factor on incidence, stability and severity of hypertension in some patients so it was decided to survey the effect of laugh in these patients. The aim of this study was to determine the effect of laughter therapy on patients with essential hypertension.METHODS: This semi-experimental study was performed on 40 patients with essential hypertension. Clinical and paraclinical evaluation was performed to exclude the secondary cause of hypertension. Patients participated in laughter clinic once a week for 2 months in Shahid Beheshti hospital. The time of these classes was 1-1.5 hours. In this clinic we tried to laugh patients with use of famous comedy films and a few inspectors attended in the meetings for supervision of virtue in performance and active cooperation of patients. Systolic and diastolic blood pressure was evaluated by mercury manometer (ALPK2) before and after every session and 24-hour blood pressure holter monitoring performed before and after study for patients that participated in all classes. Finally 35 patients participated in all sessions. Patients have been recommended for repeat of humor during week in family. FINDINGS: The mean age of patients was 55.1±10.7 years. Mean (±SD) systolic (142.9±24.1 vs. 131.1±19.8 mm/hg) and diastolic (88.4±12 vs. 81.6±10 mm/hg) blood pressure decreased significantly after every session of laughter clinic (p<0.05). Also, 24 hour holter monitoring showed significant decrease in systolic (151.9±16.3 vs. 137.1±14.2 mm/hg) and diastolic (86.7±11 vs. 79.7±9.5 mm/hg) blood pressure (p<0.05). CONCLUSION: The results showed that laughter and sense of humor is effective in short and long term (more than 2 months) effect on decreasing the blood pressure and can be used as a concomitant treatment of essential hypertension.